Regulatory framework for urban policy in some European countries: an experience for Ukraine - Цільмак, Олена Миколаївна; Цільмак, О. М.; Цильмак, Елена Николаевна; Tsilmak, Olena M.; Береза, Анатолій Валентинович; Береза, А. В.; Береза, Анатолий Валентинович; Bereza, Anatolii V.; Bereza, Anatoliy; Казміренко, В’ячеслав Петрович; Казміренко, В. П.; Казмиренко, Вячеслав Петрович; et al. (Editorial Primmate S. A. S., 2020)
The purpose of the article is to analyze the regulatory framework for urban policy in some European countries in order to emulate their positive experience and to implement it in Ukrainian legislation. Methodology. The study used general scientific and special methods of legal science, in particular, analysis and synthesis method, logical method, logical and semantic method, historical and legal method, comparative and legal method. The results of the study. The foreign practice of regulatory framework for urban policy provision, the features of its development and implementation have been considered. The content of urban policy in a number of European countries (Latvia, Finland, France and the Czech Republic) has been studied and the relevant programs implemented by the European Union have been examined. Practical implications. The experience of foreign countries has shown that State urban policy is not always set out in a single document, but as a rule is presented in several legal acts or is a component of other State programs, especially in the area of regional policy. Value/originality. The authors have proven that taking into account the peculiarities of regulatory framework for urban policy in Ukraine, it would be appropriate to adopt a separate document on urban policy that would consider the European practice and legislation of the European Union in this area, as well as the peculiarities of Ukrainian cities.

Метою статті є аналіз нормативно-правової бази забезпечення міської політики в деяких європейських країнах з метою перейняття їх позитивного досвіду та подальшого його впровадження до законодавства України. Методологія. У дослідженні використовувалися загальнонаукові та спеціальні методи юридичної науки, зокрема, метод аналізу та синтезу, логічний логіко-семантичний, історико-правовий, порівняльно-правовий методи та метод правового моделювання. Результати дослідження. Розглянуто зарубіжну практику законодавчого забезпечення міської політики, особливості її розробки та реалізації. Досліджено зміст та особливості міської політики у деяких європейських країнах (Латвії, Фінляндії, Франції та Чехії) та вивчено відповідні програми, що реалізуються Європейським Союзом. Практичні наслідки. Як свідчить аналіз досвіду зарубіжних країн, державна міська політика не завжди викладається в єдиному документі, а як правило представлена у кількох нормативно-правових актах чи є складовою інших державних програм, насамперед у сфері регіональної політики. Співвідношення / оригінальність Автори довели, що з урахуванням особливостей законодавчого регулювання міської політики в Україні,доцільним видається прийняття окремого документу з міської політики, який би враховував європейську практику та законодавство Євросоюзу у цій сфері, та особливості українських міст.
Bereza A. Regulatory framework for urban policy in some European countries: an experience for Ukraine / A. Bereza, V. Kazmirenko, O. Tsilmak, O. Melenko, O. Shvedova // Amazonia Investiga. – Vol. 9. - Issue 29. – Editorial Primmate S. A. S., 2020. – P. 507-515.
Keywords: urban policy; local government; urbanization; regional policy; spatial planning; міська політика; місцеве самоврядування; урбанізація; регіональна політика; просторове планування; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Political science